Methodology of sustainability assessment for membrane manufacturing processes - Jamil, Norhazrina (2013)
Sustainability has become new evolution of quality and efficiency indicator in any field, including product manufacturing and process itself. Key performance of certain product or process need to be quantifying throughout its life cycle, not just at designing stage but have to be further analysis over their full life cycle from manufactured up to usage and recycle stage . Sustainability product or process needs to be considered the environmental, societal and economic benefits and impact. Hence, the aim of this project is to develop sustainability framework which will determine the influencing factor of environment, social and economic in membrane manufacturing. Project will be further analysis to assess on the sustainability score for hollow fiber membrane manufacturing process in Advanced Membrane Technology Research Centre, (AMTEC) UTM. Case study was conducted on hollow fiber membrane which been derived by Poly Vinyl Chloride (PVC), NMethyl -2-2Pyrrolidone (NMP), additive and non solvent chemical. Sustainability framework developed by considering the reaction of each raw material and mixture of those chemical during the manufacturing process and categorized in three pillars of sustainability indicator. Assessment carried out using fuzzy logic approach by developing it’s linguistic variables and few more fuzzy code that require for fuzzy evaluation. Outcome of this study will illustrated the framework and sustainability score for hollow fiber membrane manufacturing that can be lead to provide solid justification for membrane manufacturer in order to evaluate the sustainability of their product and indirectly provide better and more effective water and waste water treatment